2003
DOI: 10.1046/j.1365-2443.2003.00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of Wnt signalling by HMG2L1, a novel NLK‐binding protein

Abstract: Background : Wnt signalling plays a critical role in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…The minichromosome maintenance (Mcm) proteins are essential for DNA replication, and expression of Mcm proteins implies the potential for cell proliferation. The HMG2L1, APOL6, and RBM9 genes have also been studied with cancer (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…The minichromosome maintenance (Mcm) proteins are essential for DNA replication, and expression of Mcm proteins implies the potential for cell proliferation. The HMG2L1, APOL6, and RBM9 genes have also been studied with cancer (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, expression of Axin, one of the molecules that functions to retain ␤-catenin in the complex in the cytoplasm, increased gradually during thymocyte maturation. Also HMG2L1, a nuclear negative regulator of Wnt signaling (22), was expressed at lower levels in the most immature (and also the SP) populations ( Table 1). Levels of adenomatous polyposis coli, Groucho and transcriptional activators Pygopus and Legless͞Bcl9 (7) did not change during thymocyte differentiation (Table 1).…”
Section: Expression Of Intracellular Signaling Molecules Predisposes mentioning
confidence: 99%
“…Recently, it was shown that Xenopus NLK (xNLK) binds to a novel HMG-domain containing protein HMG2L1, which can inhibit Wnt signaling in several assays (Yamada et al, 2003). In addition, xNLK binds to xSox11, another HMG-box containing transcription factor, and they cooperatively induce neural development in Xenopus (Hyodo-Miura et al, 2002).…”
Section: Nemo May Target Arm For Degradationmentioning
confidence: 99%